What Makes a Top Research Medical School? A Call for a New Model to Evaluate Academic Physicians and Medical School Performance. (May 2015) - Goldstein, Matthew J.; Lunn, Mitchell R.; Peng, Lily
<x xml:space="preserve">Abstract</x> Since the publication of the Flexner Report in 1910, the medical education enterprise has undergone many changes to ensure that medical schools meet a minimum standard for the curricula and clinical training they offer students. Although the efforts of the licensing and accrediting bodies have raised the quality of medical education, the educational processes that produce the physicians who provide the best patient care and conduct the best biomedical research have not been identified. Comparative analyses are powerful tools to understand the differences between institutions, but they are challenging to carry out. As a result, the analysis performed by U.S. News & World Report (USN&WR) has become the default tool to compare U.S. medical schools. Medical educators must explore more rigorous and equitable approaches to analyze and understand the performance of medical schools. In particular, a better understanding and more thorough evaluation of the most successful institutions in producing academic physicians with biomedical research careers are needed. In this Perspective, the authors present a new model to evaluate medical schools' production of academic physicians who advance medicine through basic, clinical, translational, and implementation science research. This model is based on relevant and accessible objective criteria that should replace the subjective criteria used in the current USN&WR rankings system. By fostering a national discussion about the most meaningful criteria that should be measured and reported, the authors hope to increase transparency of assessment standards and ultimately improve educational quality.